1986
DOI: 10.1103/physrevlett.56.2865
|View full text |Cite
|
Sign up to set email alerts
|

Universal conductance fluctuations in silicon inversion-layer nanostructures

Abstract: We measure the conductance variations of submicrometer inversion-layer segments in silicon devices, systematically changing the length, width, inelastic diffusion length, gate voltage, magnetic field, and temperature. Results agree with the theory of universal conductance fluctuations, demonstrating that random quantum interference causes rms conductance changes AG^^^e^/h in each phase-coherent subunit of each segment. The random quantum interference is extremely sensitive to change of a single scatterer.PACS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(55 citation statements)
references
References 22 publications
4
49
0
Order By: Relevance
“…Most notably in that the fluctuation pattern produced is like a set of 'finger-prints' characteristic of a particular structural, frozen-in configuration. However, the underlying mechanisms for the two phenomena are different; The UCF is a quantum interference effect usually produced by sweeping a magnetic field H that modulates G via the Aharonov-Bohm effect (similar behavior has been observed in gate experiments on diffusive samples, likewise related to an interference effect [13]). The CF observed here is associ-ated with a mechanism offered by Lee [14] to account for experiments on quasi-one dimensional hopping samples [15].…”
Section: Conductance Fluctuationsmentioning
confidence: 90%
“…Most notably in that the fluctuation pattern produced is like a set of 'finger-prints' characteristic of a particular structural, frozen-in configuration. However, the underlying mechanisms for the two phenomena are different; The UCF is a quantum interference effect usually produced by sweeping a magnetic field H that modulates G via the Aharonov-Bohm effect (similar behavior has been observed in gate experiments on diffusive samples, likewise related to an interference effect [13]). The CF observed here is associ-ated with a mechanism offered by Lee [14] to account for experiments on quasi-one dimensional hopping samples [15].…”
Section: Conductance Fluctuationsmentioning
confidence: 90%
“…4 However, it is difficult to sort out the contribution of quantum corrections to the magnetoresistance from other possible mechanisms such as two types of charge carriers and inhomogeneities.There is therefore a need for a different type of measurement sensitive solely to the mesoscopic phase coherence, such as universal conductance fluctuations (UCF). [5][6][7] It has been shown that the conductivity of sample with a given impurity concentration will fluctuate around it's average value upon changing the impurity configuration. For two dimensions these fluctuations should have a universal value of the order of e 2 h .…”
mentioning
confidence: 99%
“…The resistance as a function of gate voltage V G in Figure 1a shows the usual maximum in resistance (at the NP) with charge carrier density increasing for V G on either side of the maximum. The strong irregular fluctuations that decorate R(V G ) at low temperature are an example of universal conduction fluctuations [12][13][14][15][16][17][18] which are observed in, for example, Si inversion layers, typically below helium temperatures 14,15 . In our case, these mesoscopic resistance fluctuations (MRFs) originate from the interference of electrons scattered from a particular distribution of scattering centres as the charge carrier density is changed by varying V G .…”
mentioning
confidence: 99%